2010
DOI: 10.1021/ic9025816
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of TiO2-Derived Titanate Nanotubes Prepared by the Hydrothermal Process

Abstract: The structural change on the molecular scale of anatase-type TiO(2) during hydrothermal treatment was investigated in detail by various analytic techniques such as X-ray absorption fine structure and transmission electron microscopy in order to clarify the formation mechanisms of titanate-based nanotubes. It revealed that the nanosheet-like products composed of highly distorted TiO(6) octahedra were generated by hydrothermal treatment of anatase-type TiO(2), and then the anatase-like structures are partially b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 47 publications
8
71
1
Order By: Relevance
“…In addition, the absorption bands at 3404 and 1608 cm −1 indicates the O-H stretching mode and H-O-H bending mode, respectively. These results highlight the presence of water molecules in a interstitial position, and also the stretching vibration of water molecules produces another broad peak at 3635 cm −1 which further confirm that the samples are hydrated [40,43,45]. We have compared the current density and the peak potential changes of bare and CoHCF@TNT-modified electrodes on electrocatalytic oxidation of hydrazine, and the resulting cyclic voltammograms are shown in Figure 6.…”
Section: Ft-ir Spectral Studies For Tnt Andsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, the absorption bands at 3404 and 1608 cm −1 indicates the O-H stretching mode and H-O-H bending mode, respectively. These results highlight the presence of water molecules in a interstitial position, and also the stretching vibration of water molecules produces another broad peak at 3635 cm −1 which further confirm that the samples are hydrated [40,43,45]. We have compared the current density and the peak potential changes of bare and CoHCF@TNT-modified electrodes on electrocatalytic oxidation of hydrazine, and the resulting cyclic voltammograms are shown in Figure 6.…”
Section: Ft-ir Spectral Studies For Tnt Andsupporting
confidence: 57%
“…On the contrary, after acid treatment with a 0.1 M HCl aqueous solution, only a trace amount of sodium could be detected in this sample by EDX analysis (Figure 2(b)). This has been ascribed to the decrease of Na/Ti ratio of TiO 2 -derived TNT caused by the replacement of Na + with H + during the acid treatment with dil.HCl [40].…”
Section: Synthesis Of Tntmentioning
confidence: 99%
“…12 While TiO 2 nanoparticles can be obtained by using various techniques, hydrothermal method for the preparation of TiO 2 nanoparticle has some intrinsic advantages over other methods in producing TiO 2 nanoparticle of high degree of crystallinity, desired sizes and shapes with homogeneity in composition. 13 It favors a decrease in agglomeration among particles, narrow particle size distribution, phase homogeneity, and controlled particle morphology. 14 In a recent research, it is found that wool fabrics modified with TiO 2 nanoparticles on the surface then subsequently dyed with C. I. Reactive Blue 69 have both improved anti-felting property and better colour fastness to light.…”
Section: ·-mentioning
confidence: 99%
“…Hydrothermal synthesis is an environmentally friendly methodology used to synthesize nanostructured materials [9]. Furthermore, the hydrothermal technique is typically done using an autoclave with Teflon liners under controlled temperature and/or pressure in aqueous solutions [10].…”
Section: Introductionmentioning
confidence: 99%